PENGARUH INFORMASI ASIMETRI, UKURAN PERUSAHAAN, DAN LEVERAGE, TERHADAP MANAJEMEN LABA (EARNINGS MANAGEMENT) PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA (BEI) - Utama, Anugerah (MANABIS: Jurnal Manajemen dan Bisnis, 2022)
This research was conducted in manufacturing companies listed on the Indonesia Stock Exchange. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) with observations for 5 consecutive years, namely 2015-2019. This period was chosen because the financial statements for that period are considered to be the latest reports. Based on the above results, the simultaneous test between X1, X2, and X3 the sig value in this test is 0.000 so it can be concluded that together the variables X1, X2, and X3 have a simultaneous effect on the y variable. This result is also corroborated by the comparison between f table and f arithmetic where the value of f count is 14,897 and f table N=141 is 2,44. So it can be concluded that H01 is rejected and Ha1 is accepted because the fcount value is 14.897 > ftable 2.44. The results of individual hypothesis testing for Information Asymmetry, Firm Size, and Leverage variables show that these variables have a significant effect on the Earnings Management variable (Y) simultaneously (simultaneously). This is illustrated by the acceptance of Ha and the rejection of H0 and the significance value of X5 0.000 less than 0.05. So it can be concluded that all independent variables have a significant effect on the timeliness of submitting financial statements.